A Monomer‐Polymer‐Monomer (MPM) Organic Synthesis Strategy: Synthesis and Application of Polybenzofuran for Functionalizing Benzene Ring of Benzofuran. Issue 8 (20th May 2021) - Lu, Le; Hua, Ruimao
Abstract: To realize benzene ring functionalization of benzofuran (BF) via electrophilic aromatic substitution (S E Ar) reaction, a concise monomer‐polymer‐monomer (MPM) organic synthesis strategy is designed. It involves the steps of preparation of organic solvent‐soluble and linear polybenzofuran (PBF) from BF, S E Ar reaction of PBF, and subsequent thermal depolymerization to produce 5‐substituted BF. This consequent transformation not only presents an unusual concept for functionalizing the benzene ring of benzofuran by MPM synthetic method, but also develops an interesting route to renewable monomer by complete decomposition of polymer. In the MPM method, 2, 3‐dihydrobenzofuran is the unique structural unit in PBF, which is engaged in a S E Ar reaction in solution with excellent regiochemical selectivity to install electrophiles para to the "alkoxy" group. The substituted PBFs can then undergo thermal depolymerization under nitrogen to give 5‐substituted BFs as major products. In addition, the real‐time studies on BF polymerization in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol (HFIP) catalyzed by trifluoro‐methanesulfonic acid (TfOH) by UV‐vis spectra can directly observe the formation of cationic π‐ and σ‐complex intermediates of BF with a protonated BF at room temperature, which is further supported by the computational results using time‐dependent density functional theory (TD‐DFT). Moreover, the results of DFT theoretical calculations can also reasonably explain the complete depolymerization of PBF to re‐produce BF with high chemoselectivity and recoverable yield. Abstract : Monomer to Polymer to Monomer (MPM) Organic Synthesis Strategy : a conceptual synthetic strategy from monomer to polymer to monomer provides an efficient synthetic way for concise access to 5‐substituted BFs. MPM strategy not only enables the simple and efficient synthesis of functional compounds, which are not easily available from the traditional synthetic methodologies, but also develops a method for synthesis of functionalized polymers, which can be renewed by complete depolymerization to re‐produce the monomers.